2000
DOI: 10.1056/nejm200012143432403
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Rehospitalization for Symptomatic Venous Thromboembolism after Total Hip Arthroplasty

Abstract: In patients who underwent total hip arthroplasty, a body-mass index of 25 or greater was associated with subsequent hospitalization for thromboembolism. Pneumatic compression in patients with a body-mass index of less than 25 and prophylaxis with warfarin after discharge were independently protective against thromboembolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
145
2
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(159 citation statements)
references
References 34 publications
9
145
2
3
Order By: Relevance
“…Independent predictors of reduced early survival after VTE include increasing age, male gender, lower body mass index, confinement to a hospital or nursing home at VTE onset, congestive heart failure, chronic lung disease, serious neurological disease, and malignancy. 29- 31 We did not observe the beneficial effect of an IVC filter on short-term prognosis and it might be related to a low proportion of IVC filter implantations among these patients. This study has several advantages.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Independent predictors of reduced early survival after VTE include increasing age, male gender, lower body mass index, confinement to a hospital or nursing home at VTE onset, congestive heart failure, chronic lung disease, serious neurological disease, and malignancy. 29- 31 We did not observe the beneficial effect of an IVC filter on short-term prognosis and it might be related to a low proportion of IVC filter implantations among these patients. This study has several advantages.…”
Section: Discussionmentioning
confidence: 59%
“…Prior validation studies have shown that the codes used to define VTE in this study have a positive predictive value of approximately 90%. 30, 31 Another weakness is that DVT and PE likely remained asymptomatic in a number of patients and therefore went undetected. Thus, the true incidence of VTE in Taiwanese patients might be higher than the estimate because deaths from PE associated with other medical diseases might be under-reported.…”
Section: Discussionmentioning
confidence: 99%
“…The trend toward faster ambulation is also reflected by the shorter duration of hospital stay that we observed in the present study. White et al reported a 30% reduction in risk of venous thromboembolism in patients who were ambulatory in the first 2 days after THA, as compared with delayed ambulation (40).…”
Section: Discussionmentioning
confidence: 99%
“…This finding emphasizes the importance of early mobilization in prevention of VTE, as has been reported after total hip arthroplasty. 31 The other important finding was that bilateral simultaneous TKA was strongly associated with VTE, with over 4-fold greater odds of developing VTE compared with unilateral TKA. This effect did not disappear when we adjusted for obesity or the time to mobilization.…”
Section: Discussionmentioning
confidence: 96%